The Effect of BI Interest Rate, Exchange Rate, and Inflation on The Indonesian Sharia Stock Index (ISSI) - Katmas, Ekarina; Indarningsih, Nur Aisyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The development of the capital market has experienced quite good growth in Indonesia, including the Islamic capital market. The existence of a sharia capital market with various investment instruments such as sharia shares, sukuk, and sharia mutual funds provides investment opportunities for those who wish to invest with sharia principles. The development of sharia investment instruments, especially sharia shares, continues to show improvement. It is then supported by the Indonesia Stock Exchange (IDX) by issuing the Indonesian Sharia Stock Index (ISSI) which is a benchmark for the performance of sharia shares in Indonesia. The development of the Sharia Stock Index has continued to increase since it was published although it experienced fluctuations in several periods. It is presumably due to changes in macroeconomic variables. Therefore, the study aims to analyze the effect of the BI interest rate variable, exchange rate, and inflation on the Indonesian Sharia Stock Index (ISSI) for the period 2015 to 2020. The study uses quantitative methods, with data analysis The Error Correction Model (ECM) uses the EViews version 9 application, ECM analysis to determine long-term and short-term economic phenomena from the interaction of several research variables. The results obtained show that in the long term, the exchange rate and BI interest rate variables have an influence on the Indonesian Sharia Stock Index (ISSI) while in the short term the exchange rate variable has an influence on the Indonesian Sharia Stock Index (ISSI). Whereas, the inflation variable has no effect on the Indonesian Sharia Stock Index (ISSI) in the long and short term.